Evaluating the impact of the Extractive Industries Transparency Initiative (EITI) on corruption in Zambia. Issue 4 (November 2017) - Fenton Villar, Paul; Papyrakis, Elissaios
Highlights: Research investigating the effect of EITI in national contexts remains limited. The implementation of EITI provoked a significant decrease in corruption in Zambia. Much of this corruption-reducing effect took place at the early stages of implementation. Abstract: The Extractive Industries Transparency Initiative (EITI) is internationally recognised as a leading anti-corruption scheme, which promotes transparency, accountability and good governance of public oil, gas, and mining revenues. This article provides the first rigorous quantitative investigation of the impact of EITI on corruption in Zambia. Using a case-comparison approach, called the Synthetic Control Method (SCM), we find that the implementation of EITI provoked a significant decrease in corruption in Zambia (with the corruption-reducing effect of EITI being, though, much stronger at the earlier stages of implementation).